Respostas
respondido por:
1
2x+2y=4
x+y= -1
x+y=-1
x= -1 -y
substitui esse valor na primeira equação:
2x+2y=4
2-1-y+2y=4
1 +y=4
y=3
substitui esse valor na primeira equação pra saber o valor de x:
x=+y= -1
x+3= -1
x= -1 - 3
x= - 4
x+y= -1
x+y=-1
x= -1 -y
substitui esse valor na primeira equação:
2x+2y=4
2-1-y+2y=4
1 +y=4
y=3
substitui esse valor na primeira equação pra saber o valor de x:
x=+y= -1
x+3= -1
x= -1 - 3
x= - 4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás